Studying emotion induced by music through a crowdsourcing game. Issue 1 (January 2016) - Aljanaki, Anna; Wiering, Frans; Veltkamp, Remco C.
Highlights: We collected ground-truth data on induced musical emotion for 400 musical excerpts. We designed an online game with a purpose to attract a big number of participants. We analyzed inter-rater agreement on emotional terms from GEMS model. We found that mood, gender and liking or disliking the music influence induced emotion. We suggested improvements to GEMS scale. Abstract: One of the major reasons why people find music so enjoyable is its emotional impact. Creating emotion-based playlists is a natural way of organizing music. The usability of online music streaming services could be greatly improved by developing emotion-based access methods, and automatic music emotion recognition (MER) is the most quick and feasible way of achieving it. When resorting to music for emotional regulation purposes, users are interested in the MER method to predict their induced, or felt emotion. The progress of MER in this area is impeded by the absence of publicly accessible ground-truth data on musically induced emotion. Also, there is no consensus on the question which emotional model best fits the demands of the users and can provide an unambiguous linguistic framework to describe musical emotions. In this paper we address these problems by creating a sizeable publicly available dataset of 400 musical excerpts from four genres annotated with induced emotion. We collected the data using an online "game with a purpose" Emotify, which attracted a big and varied sample of participants. We employed a nine item domain-specific emotional model GEMS (Geneva Emotional Music Scale). In this paper we analyze the collected data and report agreement of participants on different categories of GEMS. We also analyze influence of extra-musical factors on induced emotion (gender, mood, music preferences). We suggest that modifications in GEMS model are necessary.